Sistem Pengambilan Keputusan Rektutmen Guru Paud Menerapkan Metode Simple Multi Attribute Rating Technique Exploiting Rank - Selvyanti Laia (Bulletin of Information System Research, 2023)
The procedure for recruiting PAUD teachers at the Bharlind School Medan Foundation is still done manually. As a result, the Bharlind School Medan Foundation spent a lot of time determining the results of PAUD teacher recruitment, recruitment data management was less secure, and the level of accuracy of decision making was less reliable. Because of this, the authors built a computerized decision support system for the recruitment of PAUD teachers for the Bharlind School Medan Foundation. The decision support system method applied in this decision support system is the Multi Attribute Rating Technique Exploiting Rank method. The research method used by the author for data collection in this study is the observation method. The expected results of the research are to make it easier for the Bharlind School Medan Foundation to make decisions to determine the results of PAUD Teacher Recruitment.